Fairness as comparative desert. - Wu, S. Deon (Ratio, 2022)
One prominent theory of fairness is John Broome's. This article identifies several problems with Broome's theory but defends Broome's claim that fairness requires the proportionate satisfaction of claims. This article also shows how Broome's conception of fairness is compatible with fairness as comparative desert.